A Comparative Evaluation of Efficacy of Streptococcus mutans Counts in Saliva: An in vivo Study - Sharma, Megha (Int J Clin Pediatr Dent, 2018)
Dental caries is a disease of multifactorial origin and Streptococcus mutans is considered as the chief pathogen responsible for its development. However, reduction in the number of pathogenic bacteria, particularly S. mutans, with the use of various preventive measures, can reduce dental caries to a significant level. Therefore, the present clinical study was undertaken to evaluate and compare the efficacy of toothbrushing, fluoride varnish, chlorhexidine mouthwash, and a probiotic (Yakult) in reducing the S. mutans counts in the saliva using Dentocult SM Strip Mutans kit in children. A total of 40 school students between the age group of 4 and 8 years were selected for the study and S. mutans count was taken on the first dental visit using Dentocult SM Strip Mutans test kit. After the initial scores of S. mutans were obtained, the children were divided into four groups and provided with different caries preventive regimen for 2 weeks. After 2 weeks, the scores of S. mutans were reevaluated for reduction in their counts, if any. The data thus collected were tabulated and statistically analyzed. All the groups showed a significant reduction in S. mutans counts with the highest reduction from the Fluor Protector varnish followed by chlorhexidine mouthwash, probiotic (Yakult), and toothbrushing. How to cite this article: Sharma M, Pandit IK, Srivastava N, Gugnani N, Gupta M. A Comparative Evaluation of Efficacy of Streptococcus mutans Counts in Saliva: An in vivo Study. Int J Clin Pediatr Dent 2018;11(2):94-99.